Age-to-Glasgow Coma Scale score ratio predicts gastrointestinal bleeding in patients with primary intracerebral hemorrhage - Qiu, Weizhi; Liu, Chubin; Ye, Jinfu; Wang, Gang; Yang, Fuxing; Pan, Zhigang; Hu, Weipeng; Gao, Hongzhi (Frontiers in Neurology, 2023)
Objective Recent clinical studies have demonstrated that advanced age and low initial Glasgow Coma Scale (GCS) score were independent predictors of gastrointestinal bleeding (GIB) in patients with primary intracerebral hemorrhage (ICH). However, used singly, age and GCS score have their respective shortcomings in predicting the occurrence of GIB. This study aimed to investigate the association between the age-to-initial GCS score ratio (AGR) and the risk of GIB following ICH. Methods We conducted a single-center, retrospective observational study of consecutive patients presenting with spontaneous primary ICH at our hospital from January 2017 through January 2021. Patients who fulfilled the inclusion and exclusion criteria were categorized into GIB and non-GIB groups. Univariate and multivariate logistic regression analyses were implemented to identify the independent risk factors for the occurrence of GIB, and a multicollinearity test was performed. Furthermore, one-to-one matching was conducted to balance important patient characteristics by the groups' propensity score matching (PSM) analysis. Results A total of 786 consecutive patients fulfilled the inclusion/exclusion criteria for the study, and 64 (8.14%) patients experienced GIB after primary ICH. Univariate analysis revealed that patients with GIB were significantly older [64.0 (55.0–71.75) years vs. 57.0 (51.0–66.0) years, p = 0.001] and had a higher AGR [7.32 (5.24–8.96) vs. 5.40 (4.31–7.11), p < 0.001] and a lower initial GCS score [9.0 (7.0–11.0) vs. 11.0 (8.0–13.0), p < 0.001]. The multicollinearity test revealed that no multicollinearity was observed in the multivariable models. Multivariate analysis showed that the AGR was a significant independent predictor of GIB [odds ratio (OR) 1.155, 95% confidence interval (CI) 1.041–1.281, p = 0.007], as well as prior anticoagulation or antiplatelet therapy (OR 0.388, 95% CI 0.160–0.940, p = 0.036) and MV used >24 h (OR 0.462, 95% CI 0.252–0.848, p = 0.013). Receiver operating curve (ROC) analysis illustrated that the optimal cutoff value for the AGR as a predictor for GIB in patients with primary ICH was 6.759 [the area under the curve (AUC) was 0.713 with a corresponding sensitivity of 60.94% and specificity of 70.5%, 95% CI 0.680–0.745, p < 0.001]. After 1:1 PSM, the matched GIB group had significantly higher AGR levels compared with the matched non-GIB group [7.47(5.38–9.32) vs. 5.24(4.24–6.40), p <0.001]. The ROC analysis indicated an AUC of 0.747 (the sensitivity was 65.62%, and the specificity was 75.0%, 95% CI 0.662–0.819, p < 0.001) for AGR levels as an independent predictor of GIB in patients with ICH. In addition, AGR levels were statistically correlated with unfunctional 90-day outcomes. Conclusion A higher AGR was associated with an increased risk of GIB and unfunctional 90-day outcomes in patients with primary ICH.